Independent component analyses, wavelets, neural networks, biosystems, and nanoengineering VIII : 7-9 April 2010, Orlando, Florida, United States - Independent component analyses, wavelets, neural networks, biosystems, and nanoengineering (8th : 2010 : Orlando, Florida); Szu, Harold H.; Agee, F. Jack; Society of Photo-optical Instrumentation Engineers (Bellingham, Wash. : SPIE)
Includes bibliographical references and index